Posture enhancement with cerebellum transcranial electrical stimulation: a systematic review of current methods and findings - Jahromi, Mostafa Mehraban; Vlček, Přemysl; Kvašňák, Eugen; Lippertová, Marcela Grünerová (Experimental brain research, 2024)
Recently, transcranial electrical stimulation (tES) has gained increasing popularity among researchers, especially for recovery and improvement, but interpretation of these results is difficult due to variations in study methods and outcome measurements. The main goal of this study was to better understand the postural and balance indicators affected by cerebellar tES, as the cerebellum is the main brain region responsible for controlling balance. For this systematic literature review, three databases were searched for articles where the cerebellum was stimulated by any type of tES in either healthy participants or those with neurologic disorders. Postural, dynamic, and/or static stability measurements were recorded, and risk of bias was assessed on the PEDro scale. A total of 21 studies were included in the analysis. 17 studies reported improvements after application of tES. 14 studies stimulated the cerebellum unilaterally and 15 used this modality for 20 min. Moreover, all studies exclusively used transcranial direct current as the type of stimulation. Evaluation of PEDro results showed that studies included in the analysis utilized good methodology. Although there were some inconsistencies in study results, overall, it was demonstrated that tES can improve balance and postural index under both healthy and neurological conditions. Further research of bilateral cerebellar stimulation or the use of transcranial alternating current stimulation, transcranial random noise stimulation, and transcranial pulsed current stimulation is needed for a more comprehensive assessment of the potential positive effects of cerebellar tES on the balance system.
Keywords: Transcranial electrical stimulation; mozeček; Transcranial Direct Current Stimulation; přímá transkraniální stimulace mozku; postura těla; Cerebellum; Humans; lidé; Postural Balance; posturální rovnováha; Postural stability; Posture; Review